Bridging the Gap Disciplines, Times, and Spaces in Dialogue - Volume 3 : - Coppini, Costanza (Archaeopress Publishing, 2022)
Three volumes present the proceedings of the 6th Broadening Horizons Conference, which took place at the Freie Universität Berlin from 24-28 June, 2019. This volume - Volume 3 - contains 14 papers from Session 4 - Crossing Boundaries: Connectivity and Interaction; and Session 6 - Landscape and Geography: Human Dynamics and Perceptions.